2012
DOI: 10.2135/cropsci2011.05.0248
|View full text |Cite
|
Sign up to set email alerts
|

Variability and Stability Analysis for Nutritional Traits in the Mini Core Collection of Peanut

Abstract: The nufritional quality of peanut {Arachis hypogaea L.) products depends on fhe protein content, oil content, and composition of oil. Low genefic variabllify has been a major bottleneck in genefic enhancement of these nufritional fraifs in commercial culfivars. The present sfudy was conducted fo identify stable genotypes with beffer nufrifional fraifs and good agronomic performance for use in future breeding programs. The 184 mini core accessions and four conf rol cultivars were evaluated for nufrifional traif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 25 publications
4
35
0
3
Order By: Relevance
“…The genotype AK 265 was found to be suitable for favourable situations with predictable performance as it posses high oil content with below average responsiveness (Regression coefficient bi>1) and non-significant deviation from regression line (S 2 di; p>0.05; Table 2). Results of similar nature were reported by Upadhaya et al (2012) and Kirmani et al (2013). Different sets of genes may operate in different locations and in different seasons.…”
Section: Oil Content (%)supporting
confidence: 89%
“…The genotype AK 265 was found to be suitable for favourable situations with predictable performance as it posses high oil content with below average responsiveness (Regression coefficient bi>1) and non-significant deviation from regression line (S 2 di; p>0.05; Table 2). Results of similar nature were reported by Upadhaya et al (2012) and Kirmani et al (2013). Different sets of genes may operate in different locations and in different seasons.…”
Section: Oil Content (%)supporting
confidence: 89%
“…Peanuts with high protein and low oil but with improved oil quality and rich in minerals will be the most preferred confectionery products. Efforts at ICRISAT and elsewhere have succeeded in identifying or developing peanut cultivars with variation in seed size, protein, oil content, and oil quality (Upadhyaya et al, 2012), but no concerted efforts were made to identify sources of the essential minerals such as Fe and Zn. The genebank at ICRISAT in Patancheru, India, maintains a large global collection (15,445 accessions) of peanut germplasm.…”
mentioning
confidence: 99%
“…The genotypes ICGV 02038, TG LPS 3, Faizpur 1-5, and ICGV 01276 recorded high protein content of 26-28% among the GSP. Significant effect of environment and genotype × environment interactions for protein content in groundnut (Dwivedi et al, 1993, Upadhyaya et al, 2012 indicated the need to test the performance of the genotypes in different growing environments before using in breeding programs. One genotype in the GSP, SunOleic 95R, an introduction from the USA recorded high oleic acid content of 74%, indicating a strong need to breed high oleic groundnut lines.…”
Section: Resultsmentioning
confidence: 99%